2003
DOI: 10.1590/s1677-55382003000200007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the technique of cryopreservation and dilution/centrifugation after thawing on the motility and vitality of spermatozoa of oligoasthenozoospermic men

Abstract: For human semen samples with low initial quality, freezing through vapor technique or through the automated technique showed to be equivalent in regarding recovery of live spermatozoa with progressive motility. The effects of dilution and centrifugation to remove the cryoprotector had a negative impact only in samples frozen through the automated technique. In both techniques, progressive motility is kept constant during the first 3 hours after thawing and removal of the cryoprotector, but is drastically dimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The use of glycerol to prevent injury to human spermatozoa during cryopreservation is well established (18), and its association with buffers, such as Tris (hydroximethyl amino metano) and TES (n-Tris [hydroximethyl] methyl-2-amino-ethane sulphonic acid), and eggyolk yield optimal cryosurvival rates (19). Slow freezing using programmable freezing machines or fast freezing, as used in this study, seems to have no direct effect on thaw survival both in normal and poor quality sperm (20). It has been demonstrated that, independently from the freezing technique, motility from poor quality sperm is kept constant during the first 3 hours after thawing, but it is drastically reduced by the end of an incubation period of 24 hours (20).…”
Section: Commentsmentioning
confidence: 69%
See 1 more Smart Citation
“…The use of glycerol to prevent injury to human spermatozoa during cryopreservation is well established (18), and its association with buffers, such as Tris (hydroximethyl amino metano) and TES (n-Tris [hydroximethyl] methyl-2-amino-ethane sulphonic acid), and eggyolk yield optimal cryosurvival rates (19). Slow freezing using programmable freezing machines or fast freezing, as used in this study, seems to have no direct effect on thaw survival both in normal and poor quality sperm (20). It has been demonstrated that, independently from the freezing technique, motility from poor quality sperm is kept constant during the first 3 hours after thawing, but it is drastically reduced by the end of an incubation period of 24 hours (20).…”
Section: Commentsmentioning
confidence: 69%
“…It has been demonstrated that, independently from the freezing technique, motility from poor quality sperm is kept constant during the first 3 hours after thawing, but it is drastically reduced by the end of an incubation period of 24 hours (20). In this study, we used a rapid vapor freezing method because it is less expensive, time-consuming and labor-intensive, and it has proven equally effective in the recovery of post-thaw motile sperm (20,21).…”
Section: Commentsmentioning
confidence: 99%
“…The semi-synthetic clerodanes MHDCTN and PHDCTN were synthesized and characterized according to the literature. 14 …”
Section: Methodsmentioning
confidence: 99%
“…Among these factors, consumption of caffeine (1,3,7‐trimethylxanthine), a substance found naturally or as an additive in many foods and drugs, has effects on the reproductive system and correlates with increased risk of spontaneous abortion; reduction of female fertility; and increased sperm concentration, motility and serum testosterone levels (Klonoff‐Cohen et al ., ; Jensen et al ., ). Although its mechanism is not fully elucidated, caffeine acts as inhibitor of phosphodiesterase enzyme, which is responsible for the breakdown of cyclic adenosine monophosphate (cAMP), thus triggering an increase in the concentration of intracellular cAMP and allowing the energy metabolism of spermatozoa to rise (Esteves et al ., ; Li et al ., ). As energy expenditure is one of the factors involved in the decrease in sperm fertilisation capacity after cryopreservation, the potential increase in energy concentration inside the cell caused by caffeine should be investigated in humans (Esteves et al ., ; Li et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Although its mechanism is not fully elucidated, caffeine acts as inhibitor of phosphodiesterase enzyme, which is responsible for the breakdown of cyclic adenosine monophosphate (cAMP), thus triggering an increase in the concentration of intracellular cAMP and allowing the energy metabolism of spermatozoa to rise (Esteves et al ., ; Li et al ., ). As energy expenditure is one of the factors involved in the decrease in sperm fertilisation capacity after cryopreservation, the potential increase in energy concentration inside the cell caused by caffeine should be investigated in humans (Esteves et al ., ; Li et al ., ). Indeed, in vitro tests on animal models have reported that the addition of caffeine to semen samples increases motility and stimulates capacitation and spontaneous acrosome reaction of the spermatozoa (Yamaguchi et al ., ; Yamaguchi & Funahashi, ).…”
Section: Introductionmentioning
confidence: 99%